Contemporary Challenges in Teaching and Learning Hadith - Yoga Adhitya Fredy Firmansyah; Achmad Saifu Dzulfiqar; Indina Ulil Fasya; Lailatul Choiriyah (LPPM UIN Syekh Wasil Kediri, 2025)
This study aims to analyse learning strategies derived from the hadiths of the Prophet Muhammad (SAW) and identify the challenges of implementing them in the modern era. Using a qualitative literature review approach through the Systematic Literature Review (SLR) method, this study examines scientific works, classical hadith sources, and contemporary educational studies relevant to hadith-based learning. The results of the study show that the Prophet Muhammad (SAW) employed various pedagogical strategies, including educational lectures, discussions, question-and-answer sessions, and exemplary behavior, which were effective in enhancing students' understanding, participation, and character development. These strategies align with modern educational principles that emphasize student-centered learning, dialogic interaction, contextual understanding, and humanistic values. However, the implementation of hadith-based learning strategies in the contemporary era still faces a number of challenges, including low hadith literacy, the dominance of textual and teacher-centred approaches, limited pedagogical competence among educators, and the proliferation of unverified religious information in digital media. Nevertheless, the integration of hadith-based learning strategies with contemporary pedagogical approaches has significant potential to enhance the relevance, effectiveness, and meaningfulness of hadith education. Therefore, hadiths serve not only as a normative religious source but also as a strategic foundation in the development of modern Islamic education.